Outcome and Patterns of Care in Advanced Biliary Tract Carcinoma (ABC): Experience from Two Tertiary Institutions in the United Kingdom. Issue 2 (March 2014) - Huggett, Matthew T; Passant, Helen; Hurt, Chris; Pereira, Stephen P; Bridgewater, John; Mukherjee, Somnath
Aims and Background: The ABC-02 trial has defined the standard therapy for patients with advanced biliary tract cancer (ABC); however, outcome in an unselected patient population in the UK has not been described. We aimed to investigate the outcome of a series of patients with ABC from two large UK cancer networks. Methods and Study Design: We retrospectively reviewed all cases of ABC presenting to two UK cancer networks over a nine-year period. Overall survival (OS) and factors influencing OS were assessed. Results: Four hundred and two patients were available for analysis. The median OS was 6.2 months. On univariate analysis, age ≥70 years (P = 0.047), advanced disease stage (P <0.001), gall bladder primary (P = 0.033), poor performance status (P <0.001) and lack of chemotherapy (P <0.001) were associated with worse outcome. Survival was superior in the 36.4% of patients who received palliative chemotherapy (12.5 vs 4.3 months; P <0.001). On multivariate analysis of patients who had chemotherapy, those who did not receive fluoropyrimidine-based regimens (HR = 5.12; P = 0.022) or gemcitabine-based regimens (HR = 5.01; P = 0.021) had a higher mortality, whereas the effect of platinum-containing regimens was of borderline significance (HR = 2.23; P = 0.086). Sites, age, and multi-agent regimens were not significant. Conclusions: This is one of the largest retrospective studies reporting outcome of palliative chemotherapy for ABC. It confirms the benefit of palliative chemotherapy in an unselected group of patients. Fluoropyrimidine-based regimens appear to be as effective as gemcitabine-based treatments.